2021
DOI: 10.1002/ygh2.444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vedolizumab dose intensification on serum drug concentrations and regain of response in inflammatory bowel disease patients with secondary loss of response

Abstract: Background and Aims Dose intensification of vedolizumab (VDZ) for moderate‐to‐severe ulcerative colitis (UC) and Crohn's disease (CD) may be effective in patients losing response. We aimed to assess the clinical and pharmacokinetic effect of VDZ dose intensification. Methods We performed a multicentre open‐label prospective study from June 2017 through December 2018 in patients on VDZ losing response, defined as total Mayo score >6 (UC) or Harvey‐Bradshaw Index >4 with inflammation (CD). Blood samples and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
(39 reference statements)
2
12
0
Order By: Relevance
“…A literature review (box 1) identified seven studies (four observational studies and three single arm open-label studies), with 411 patients with IBD, that examined the effect of dose escalation for patients experiencing a LOR (table 1). 10–16 The criteria for dose escalation for LOR varied between studies, particularly in patients with UC. The definition for response and remission were also heterogeneous with different scoring systems being used and some using a physician’s assessment (table 1).…”
Section: Evidence To Support Dose Escalation In Patients With Asecond...mentioning
confidence: 99%
See 4 more Smart Citations
“…A literature review (box 1) identified seven studies (four observational studies and three single arm open-label studies), with 411 patients with IBD, that examined the effect of dose escalation for patients experiencing a LOR (table 1). 10–16 The criteria for dose escalation for LOR varied between studies, particularly in patients with UC. The definition for response and remission were also heterogeneous with different scoring systems being used and some using a physician’s assessment (table 1).…”
Section: Evidence To Support Dose Escalation In Patients With Asecond...mentioning
confidence: 99%
“…The results from six studies of dose escalation for LOR in people with CD show an overall response rate of 47%–61% and remission rate of 14%–34% reported for various time-points from 8 to 52 weeks 10 12–16. In UC, the response rate was 32%–63% and remission rate was 11%–34% reported for timepoints between 4 and 52 weeks 11 13–16.…”
Section: Evidence To Support Dose Escalation In Patients With Asecond...mentioning
confidence: 99%
See 3 more Smart Citations